Laminate, negative electrode current collector for lithium ion secondary battery, and negative electrode for lithium ion secondary battery

A laminate structure with a copper-nickel gradient in the second metal layer addresses cracking issues in negative electrode current collectors, enhancing tensile strength and preventing structural failure in lithium ion secondary batteries.

JP7607680B2Active Publication Date: 2024-12-27TDK CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022577040
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-20
Filing Date
2021-12-16
Publication Date
2024-12-27
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

Negative electrode current collectors for lithium ion secondary batteries are susceptible to cracking and breaking due to repeated tensile stress caused by volume changes in the negative electrode active material layer during charging and discharging, leading to deformation of the battery body or short circuits.

Method used

A laminate structure comprising a copper-based first metal layer and a nickel-based second metal layer with varying nickel content along its thickness direction, where the nickel content increases from the interface with the first metal layer to the opposite surface, enhancing tensile strength by gradient modulation of the second metal layer's elastic modulus.

Benefits of technology

The laminate structure effectively suppresses cracking and breaking under tensile stress, maintaining structural integrity and preventing short circuits, thereby improving the durability and performance of lithium ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607680000002
    Figure 0007607680000002
  • Figure 0007607680000003
    Figure 0007607680000003
  • Figure 0007607680000004
    Figure 0007607680000004
Patent Text Reader

Abstract

This layered body includes a first metal layer that includes copper, and a second metal layer that includes nickel and is layered directly on the first metal layer. A first surface of the second metal layer is the surface contacting the first metal layer. A second surface of the second metal layer is the opposite surface from the first surface. The thickness direction of the second metal layer is substantially perpendicular to the first surface, and is the direction from the first surface toward the second surface. The unit of the nickel content in the second metal layer is mass%. The nickel content in the second metal layer increases along the thickness direction.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate, a negative electrode current collector for a lithium ion secondary battery, and a negative electrode for a lithium ion secondary battery. [Background technology]

[0002] A negative electrode current collector for a lithium ion secondary battery is subjected to repeated loads (compressive stress and tensile stress) due to the volume of the negative electrode active material layer laminated on the negative electrode current collector fluctuating with charging and discharging. The deformation of the negative electrode current collector due to this load causes deformation of the battery body or a short circuit between the electrodes. Therefore, the negative electrode current collector is required to have durability (high tensile strength) against the load (especially tensile stress). For example, the following Patent Document 1 discloses a negative electrode current collector in which an electrode foil and a hard nickel plating layer are laminated as a negative electrode current collector having tensile strength. The following Patent Document 2 discloses a current collector in which a first metal layer made of copper and a second metal layer made of nickel or a nickel alloy are laminated as a current collector having sufficient strength to suppress cracking and tearing. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-197205 A [Patent Document 2] JP 2019-186134 A Summary of the Invention [Problem to be solved by the invention]

[0004] When a laminate made of multiple metal layers is subjected to tensile stress, cracks form in the metal layers and propagate and eventually break the metal layers or the laminate.

[0005] An object of one aspect of the present invention is to provide a laminate having high tensile strength, and a negative electrode current collector and a negative electrode for a lithium ion secondary battery including the laminate. [Means for solving the problem]

[0006] A laminate according to one aspect of the present invention comprises a first metal layer containing copper and a second metal layer containing nickel and laminated directly on the first metal layer, wherein a first surface of the second metal layer is a surface in contact with the first metal layer, a second surface of the second metal layer is a surface opposite to the first surface, a thickness direction of the second metal layer is approximately perpendicular to the first surface and is a direction from the first surface to the second surface, the nickel content of the second metal layer is expressed in units of mass%, and the nickel content of the second metal layer increases along the thickness direction.

[0007] The second metal layer may further include at least one element selected from the group consisting of phosphorus and tungsten.

[0008] The second metal layer may be composed of a plurality of nickel-containing layers stacked in the thickness direction, and the nickel content of each of the plurality of nickel-containing layers may be different from each other.

[0009] The thickness of the first metal layer is designated T1 and the thickness of the second metal layer is designated T2, where T2 / T1 may be 0.6 or more and 1.0 or less.

[0010] The nickel content of the second metal layer may be lowest near the first surface, may increase stepwise along the thickness direction, and may be highest near the second surface.

[0011] The nickel content in the second metal layer may be lowest near the first surface, may increase continuously along the thickness direction, and may be highest near the second surface.

[0012] A negative electrode current collector for a lithium ion secondary battery according to one aspect of the present invention includes the above laminate.

[0013] A negative electrode for a lithium ion secondary battery according to one aspect of the present invention includes the above-described negative electrode current collector and a negative electrode active material layer containing a negative electrode active material, where the negative electrode active material layer is laminated directly on the second surface of the second metal layer.

[0014] The negative electrode active material may contain silicon. Effect of the Invention

[0015] According to one aspect of the present invention, there is provided a laminate having high tensile strength, and a negative electrode current collector and a negative electrode for a lithium ion secondary battery including the laminate. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is a schematic perspective view of a laminate (negative electrode current collector) according to one embodiment of the present invention, and a negative electrode including the laminate. [Diagram 2] FIG. 2 is a graph showing an example of the distribution of the nickel content in the second metal layer. [Diagram 3] FIG. 3 is a graph showing another example of the distribution of the nickel content in the second metal layer. [Figure 4] FIG. 4 is a schematic diagram showing an outline of a bending test for evaluating the tensile strength of a laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings. In the drawings, the same components are designated by the same reference numerals. The present invention is not limited to the following embodiments.

[0018] The laminate according to the present embodiment is a negative electrode current collector for a lithium ion secondary battery. As shown in FIG. 1, the laminate 10 according to the present embodiment has a first metal layer 1 and a second metal layer 2. The first metal layer 1 contains copper (Cu). The second metal layer 2 contains nickel (Ni). In the case of the laminate 10 shown in FIG. 1, the second metal layer 2 is directly laminated on both surfaces of the first metal layer 1. However, the second metal layer 2 may be directly laminated on only one surface of the first metal layer 1. The first surface S1 of the second metal layer 2 is a surface in contact with the first metal layer 1. The first surface S1 of the second metal layer 2 may be rephrased as an interface between the first metal layer 1 and the second metal layer 2. The second surface S2 of the second metal layer 2 is a back surface of the first surface S1. The thickness direction D of the second metal layer 2 is approximately perpendicular to the first surface S1 and is a direction from the first surface S1 to the second surface S2.

[0019] 1, the negative electrode 20 for a lithium ion secondary battery according to this embodiment includes a laminate 10 (negative electrode current collector) and a negative electrode active material layer 3. The negative electrode active material layer 3 includes a negative electrode active material. The negative electrode active material layer 3 is laminated directly on the second surface S2 of each second metal layer 2. The lithium ion secondary battery according to this embodiment may include a negative electrode 20, a positive electrode, a separator, and an electrolyte. The separator and the electrolyte are disposed between the negative electrode 20 and the positive electrode. The electrolyte permeates the separator. The positive electrode may include a positive electrode current collector and a positive electrode active material layer laminated on the positive electrode current collector. For example, the positive electrode current collector may be an aluminum foil or a nickel foil. The positive electrode active material layer includes a positive electrode active material. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium manganese spinel (LiMn2O4), LiNi x Co y Mn z M aO2 (x + y + z + a = 1, 0 ≤ x < 1, 0 ≤ y < 1, 0 ≤ z < 1, 0 ≤ a < 1, M is one or more elements selected from the group consisting of Al, Mg, Nb, Ti, Cu, Zn, and Cr), lithium vanadium compound (LiV2O5), olivine-type LiMPO4 (M is one or more elements selected from Co, Ni, Mn, Fe, Mg, Nb, Ti, Al, and Zr, or VO), lithium titanate (Li4Ti5O 12 )、LiNi x Co y Al z O2 (0.9 < x + y + z < 1.1), which may be one or more compounds selected from the group consisting of polyacetylene, polyaniline, polypyrrole, polythiophene, and polyacene. The positive electrode active material layer may further contain a conductive aid such as carbon or metal powder. The positive electrode active material layer may further contain a binder (adhesive or resin). The separator may be one or more porous polymer films (films or laminates) having electrical insulation. The electrolyte contains a solvent and an electrolyte (lithium salt). The solvent may be water or an organic solvent. For example, the electrolyte (lithium salt) may be one or more lithium compounds selected from the group consisting of LiPF6, LiClO4, LiBF4, LiCF3SO3, LiCF3CF2SO3, LiC(CF3SO2)3, LiN(CF3SO2)2, LiN(CF3CF2SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(CF3CF2CO)2, and LiBOB.

[0020] The unit of the Ni content in the second metal layer 2 is mass %. The Ni content in the second metal layer 2 increases along the thickness direction D of the second metal layer 2. That is, the Ni content in the second metal layer 2 is lowest near the first surface S1, increases gradually or stepwise from the first surface S1 toward the second surface S2, and is highest near the second surface S2. The graph in FIG. 2 shows an example of the distribution of the Ni content in the second metal layer 2. The horizontal axis of the graph in FIG. 2 is the distance d from the first surface S1 in the thickness direction D of the second metal layer 2. The vertical axis of the graph in FIG. 2 is the Ni content ([Ni]) at a position in the second metal layer 2 that is a distance d from the first surface S1. As shown in FIG. 2, the Ni content in the second metal layer 2 may increase continuously (gradually) along the thickness direction D. The distribution of the Ni content in the second metal layer 2 may be represented by a straight line. The distribution of the Ni content in the second metal layer 2 may be represented by a curve.

[0021] The Ni content in the second metal layer 2 increases along the thickness direction D, allowing the laminate 10 to have high tensile strength. Tensile strength refers to the durability of the laminate 10 against tensile stress in a direction parallel to the surface of the second metal layer 2. The mechanism by which the laminate 10 has high tensile strength is as follows. However, the following mechanism is hypothetical, and the technical scope of the present invention is not limited by the following mechanism.

[0022] Since laminate 10 has not only first metal layer 1 but also second metal layer 2 laminated on first metal layer 1, laminate 10 can have a higher tensile strength than a conventional current collector consisting of only one metal layer containing Cu. However, the high tensile strength of laminate 10 is due not only to the laminate structure but also to the Ni content that increases in second metal layer 2 along the thickness direction D. The higher the Ni content in the second metal layer 2, the lower the elastic modulus of the second metal layer 2. The lower the elastic modulus of the second metal layer 2, the softer the second metal layer 2. Therefore, the lower the elastic modulus of the second metal layer 2, the more easily the second metal layer 2 deforms in response to tensile stress, and the more easily cracks and breaks in the second metal layer 2 due to deformation of the second metal layer 2 are suppressed. On the other hand, the lower the Ni content in the second metal layer 2, the higher the elastic modulus of the second metal layer 2. The higher the elastic modulus of the second metal layer 2, the harder the second metal layer 2. Therefore, the higher the elastic modulus of the second metal layer 2, the more difficult it is for the second metal layer 2 to deform in response to tensile stress, and the more likely it is that cracks and breaks will occur in the second metal layer 2 due to deformation of the second metal layer 2. Since the content of Ni in the second metal layer 2 increases along the thickness direction D, the elastic modulus of the second metal layer 2 decreases along the thickness direction D. That is, the elastic modulus of the second metal layer 2 is highest near the first surface S1, gradually or stepwise decreases from the first surface S1 toward the second surface S2, and is lowest near the second surface S2. Therefore, the second surface S2 having the lowest elastic modulus of the second metal layer 2 contacts the negative electrode active material layer 3. As a result, the second metal layer 2 is easily deformed in response to the tensile stress repeatedly acting on the second surface S2 due to the volumetric fluctuation of the negative electrode active material layer 3, and cracks and breaks in the second metal layer 2 due to the deformation of the second metal layer 2 are suppressed. That is, the second surface S2 side, which is easily deformed due to the volumetric fluctuation of the negative electrode active material layer 3, has a sufficiently low elastic modulus to suppress cracks and breaks due to deformation, and the first surface S1 side, which is not easily affected by the volumetric fluctuation of the negative electrode active material layer 3, has sufficient hardness (high elastic modulus), so that a sufficiently high tensile strength of the entire second metal layer 2 is achieved. In other words, as the elastic modulus of the second metal layer 2 decreases gradually or in steps from the first surface S1 to the second surface S2, the stress acting on the second metal layer 2 due to the volumetric fluctuation of the negative electrode active material layer 3 is dispersed, and cracks and breaks in the second metal layer 2 due to deformation of the second metal layer 2 are suppressed.

[0023] In order to increase the energy density of a lithium-ion secondary battery, the negative electrode housed in a battery package is wound or folded in a rolled state in a state where it is laminated with a separator, an electrolyte, and a positive electrode. Since stress is likely to act on the folded portion of the laminate (negative electrode current collector) constituting the negative electrode, cracks and breaks are likely to occur at the folded portion of the conventional laminate. On the other hand, since the laminate 10 according to this embodiment has high mechanical strength (especially tensile strength), cracks and breaks are suppressed at the folded portion of the laminate 10.

[0024] The second metal layer 2 may be composed of a plurality of nickel-containing layers stacked in the thickness direction D, and the Ni content of each of the plurality of nickel-containing layers may be different from each other. In other words, the plurality of nickel-containing layers may be distinguished from each other based on the Ni content. In each nickel-containing layer, the Ni content may be constant. In each nickel-containing layer, the Ni content may increase along the thickness direction D. The thickness of each nickel-containing layer may be uniform. The number n of nickel-containing layers constituting the second metal layer 2 is an integer of 2 or more and is not particularly limited. For example, any pair of nickel-containing layers constituting the second metal layer 2 is represented as the (k-1)th nickel-containing layer and the kth nickel-containing layer. k is any integer of 2 or more and n or less. The kth nickel-containing layer is directly stacked on the (k-1)th nickel-containing layer in the thickness direction D of the second metal layer 2. When k is 2, the (k-1)th nickel-containing layer (i.e., the first nickel-containing layer) is directly stacked on the first metal layer 1. The distance between the first metal layer 1 and the k-th nickel-containing layer is greater than the distance between the first metal layer 1 and the (k-1)th nickel-containing layer, and the Ni content in the k-th nickel-containing layer is higher than the Ni content in the (k-1)th nickel-containing layer.

[0025] For example, when the number n of nickel-containing layers constituting the second metal layer 2 is 3, the second metal layer 2 is composed of a first nickel-containing layer, a second nickel-containing layer, and a third nickel-containing layer. The first nickel-containing layer is directly laminated on the first metal layer 1, the second nickel-containing layer is directly laminated on the first nickel-containing layer, and the third nickel-containing layer is directly laminated on the second nickel-containing layer. The graph in FIG. 3 shows the distribution of the Ni content in the second metal layer 2 when n is 3. The horizontal axis of the graph in FIG. 3 is the same as the horizontal axis of the graph in FIG. 2, and the vertical axis of the graph in FIG. 3 is the same as the vertical axis of the graph in FIG. 2. As shown in FIG. 3, the Ni content in the third nickel-containing layer L3 is higher than the Ni content in the second nickel-containing layer L2, and the Ni content in the second nickel-containing layer L2 is higher than the Ni content in the first nickel-containing layer L1. The Ni content may be constant within each of the first nickel-containing layer L1, the second nickel-containing layer L2, and the third nickel-containing layer L3, and the Ni content in the second metal layer 2 may increase stepwise along the thickness direction D.

[0026] Ni may be the main component of the second metal layer 2. In other words, when the second metal layer 2 contains a plurality of elements, the Ni content may be the highest. The Ni content in the second metal layer 2 may be, for example, 60% by mass or more and less than 100% by mass, or 60% by mass or more and 99% by mass or less. When the second metal layer 2 contains three or more elements, the Ni content in the second metal layer 2 may be less than 50% by mass. A part of the second metal layer 2 may be simple Ni. At least a part or the whole of the second metal layer 2 may be an alloy containing Ni, or an intermetallic compound containing Ni. When the Ni content in the second metal layer 2 is within the above range, the laminate 10 is likely to have high tensile strength.

[0027] The Ni content in the second metal layer 2 is minimum in the vicinity of the first surface S1 of the second metal layer 2. The minimum value of the Ni content in the second metal layer 2 is [Ni] MIN The Ni content in the second metal layer 2 is maximum in the vicinity of the second surface S2 of the second metal layer 2. The maximum value of the Ni content in the second metal layer 2 is [Ni] MAXΔ[Ni] is expressed as [Ni] MAX -[Ni] MIN It is defined as follows. Δ[Ni] may be 1 mass % or more and 15 mass % or less, or 5 mass % or more and 12 mass % or less. When Δ[Ni] is within the above range, the laminate 10 tends to have high tensile strength.

[0028] The second metal layer 2 may further contain at least one element (additive element) selected from the group consisting of phosphorus (P) and tungsten (W). Of all the elements constituting the second metal layer 2, all elements other than Ni may be additive elements. The total content of the additive elements in the second metal layer 2 decreases along the thickness direction D of the second metal layer 2, and the Ni content in the second metal layer 2 increases along the thickness direction D of the second metal layer 2. In other words, the total content of the additive elements in the second metal layer 2 is highest near the first surface S1, gradually or stepwise decreases from the first surface S1 to the second surface S2, and is lowest near the second surface S2. The second metal layer 2 may further contain additive elements other than P and W. When the second metal layer 2 contains additive elements other than P and W, the second metal layer 2 does not need to contain P and W.

[0029] The second metal layer 2 may be formed by electrolytic plating or electroless plating. The second metal layer 2 formed by electrolytic plating or electroless plating may be heat-treated. As shown in the examples described later, the electrolytic plating or electroless plating can increase the Ni content in the second metal layer 2 along the thickness direction D of the second metal layer 2. For example, the control factors for the distribution of the Ni content in the second metal layer 2 may be the composition of the plating solution, the content and ratio of each raw material in the plating solution, the temperature of the plating solution, the pH of the plating solution, the current density of the first metal layer 1, and the plating time. The raw material contained in the plating solution may be, for example, a compound containing Ni and a compound containing the above-mentioned additive element. The higher the content of the Ni-containing compound in the plating solution used to form each nickel-containing layer, the higher the Ni content in each nickel-containing layer. The second metal layer 2 may be formed of a plurality of nickel-containing layers having different Ni contents by carrying out a plurality of plating processes with different control factors. That is, the Ni content in each of the multiple nickel-containing layers constituting the second metal layer 2 may be controlled so that the Ni content in the second metal layer 2 increases along the thickness direction D of the second metal layer 2. The current density of the first metal layer during electrolytic plating may be increased continuously or stepwise over time to form a second metal layer 2 in which the Ni content increases along the thickness direction D.

[0030] Cu may be the main component of the first metal layer 1. The first metal layer 1 may consist only of Cu. The first metal layer 1 may consist of an alloy containing Cu. When the first metal layer 1 contains Cu, the laminate 10 can have high conductivity required for a negative electrode current collector for a lithium ion secondary battery.

[0031] The negative electrode active material contained in the negative electrode active material layer 3 may be any material that can occlude and release lithium ions, and is not particularly limited. For example, the negative electrode active material contained in the negative electrode active material layer 3 may contain silicon (Si). The negative electrode active material containing silicon is more likely to expand and contract with the charge and discharge of the lithium ion secondary battery than other negative electrode active materials. Due to the volume fluctuation of the negative electrode active material layer 3 accompanying charge and discharge, the laminate 10 (second metal layer 2) receives repeated tensile stress. However, since the laminate 10 according to the present embodiment has high tensile strength, breakage of the laminate 10 due to volume fluctuation of the negative electrode active material layer 3 is suppressed.

[0032] The negative electrode active material containing silicon may be a simple substance of silicon, an alloy containing silicon, or a compound containing silicon (such as an oxide or a silicate). For example, the alloy containing silicon may contain at least one element selected from the group consisting of tin (Sn), nickel (Ni), copper (Cu), iron (Fe), cobalt (Co), manganese (Mn), zinc (Zn), indium (In), silver (Ag), titanium (Ti), germanium (Ge), bismuth (Bi), antimony (Sb), and chromium (Cr). For example, the compound containing silicon may contain at least one element selected from the group consisting of boron (B), nitrogen (N), oxygen (O), and carbon (C). For example, the negative electrode active material containing silicon may be at least one compound selected from the group consisting of SiB4, SiB6, Mg2Si, Ni2Si, TiSi2, MoSi2, CoSi2, NiSi2, CaSi2, CrSi2, Cu5Si, FeSi2, MnSi2, NbSi2, TaSi2, VSi2, WSi2, ZnSi2, SiC, Si2N2, Si2N2O, SiO X (0 < X ≦ 2) and at least one compound selected from the group consisting of LiSiO. The negative electrode active material may be a fiber containing silicon (such as a nanowire) or a particle containing silicon (such as a nanoparticle). The negative electrode active material layer 3 may further contain a binder. The binder binds the negative electrode active materials to each other and binds the negative electrode active material layer 3 to the surface of the second metal layer 2.

[0033] The thickness T1 of the first metal layer 1 may be, for example, 1 μm or more and 8 μm or less. The thickness T2 of one second metal layer 2 may be, for example, 0.3 μm or more and 4 μm or less, or 1.0 μm or more and 2 μm or less. The sum of the thicknesses T2 of the multiple second metal layers 2 is T2 TOTAL and T2 TOTAL / T1 may be 0.6 or more and 1.0 or less. For example, as shown in FIG. 1, when the laminate 10 has two second metal layers 2, T2 TOTAL is the sum of the thicknesses of the two second metal layers 2. TOTAL When / T1 is 0.6 or more, the laminate 10 tends to have a sufficiently high tensile strength. TOTAL The smaller / T1 is, the lower the cost of the raw materials for the laminate 10 (second metal layer 2). TOTAL When / T1 is 1.0 or less, a lithium ion secondary battery including the laminate 10 is likely to have a sufficiently high energy density. Even when the laminate 10 includes only one second metal layer 2, T2 / T1 may be 0.6 or more and 1.0 or less for the same reason as above. The thickness T3 of one negative electrode active material layer 3 may be, for example, 10 μm or more and 300 μm or less. The thickness T1 of the first metal layer 1, the thickness T2 of the second metal layer 2, and the thickness T3 of the negative electrode active material layer 3 may each be uniform.

[0034] The dimensions of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be approximately the same as each other. For example, the width of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be several tens of mm or more and several hundreds of mm or less. The length of the first metal layer 1, the second metal layer 2, and the negative electrode active material layer 3 in the direction perpendicular to the stacking direction may be several tens of mm or more and several thousands of mm or less.

[0035] The present invention is not necessarily limited to the above-described embodiment. Various modifications of the present invention are possible without departing from the spirit of the present invention, and these modifications are also included in the present invention.

[0036] For example, the second metal layer may be formed by a vapor deposition process, which may be, for example, a metal-organic physical vapor deposition (MOPVD) process, such as sputtering, or a metal-organic chemical vapor deposition (MOCVD) process.

[0037] The laminate according to the present invention may be used as a heat dissipation material or an electromagnetic wave shielding material. Tensile stress acts on the heat dissipation material or the electromagnetic wave shielding material during processing. Since the laminate according to the present invention has high tensile strength, damage to the heat dissipation material or the electromagnetic wave shielding material during processing can be suppressed. EXAMPLES

[0038] The present invention will be described in detail with reference to the following examples and comparative examples, but the present invention is not limited to the following examples.

[0039] [Pretreatment of the first metal layer] A commercially available electrolytic copper foil was used as the first metal layer. The thickness of the first metal layer was 4.5 μm. The thickness of the first metal layer was uniform. The first metal layer was immersed in an acidic degreasing solution for 1 minute to remove organic matter adhering to the surface of the first metal layer. As the degreasing solution, Thru-cup MSC-3-A manufactured by Uemura Kogyo Co., Ltd. was used. After degreasing, the first metal layer was cleaned by immersing it in pure water for 1 minute.

[0040] After cleaning, the first metal layer was immersed in dilute sulfuric acid for 1 minute to remove the native oxide film present on the surface of the first metal layer. The concentration of the dilute sulfuric acid was 10 mass %. After removing the native oxide film, the first metal layer was immersed in pure water for 1 minute to clean the first metal layer.

[0041] Using the first metal layer that had been subjected to the above pretreatment, laminates of Examples 1 to 13 and Comparative Examples 1 to 5 were produced by the following method.

[0042] Example 1 The second metal layer was formed on both surfaces of the first metal layer by the following electrolytic plating, i.e., a laminate was formed by the electrolytic plating, which was composed of the first metal layer and the second metal layer laminated on both surfaces of the first metal layer. The second metal layer in Example 1 was composed of a first nickel-containing layer L1 laminated directly on the surface of the first metal layer, a second nickel-containing layer L2 laminated directly on the first nickel-containing layer L1, and a third nickel-containing layer L3 laminated directly on the second nickel-containing layer L2. The surface of the first nickel-containing layer L1 in contact with the first metal layer corresponds to the first surface of the second metal layer.

[0043] In the electrolytic plating, the first metal layer and the other electrodes connected to a power source were immersed in a plating solution, and a current was applied to the first metal layer and the other electrodes. The plating solution contained nickel sulfate hexahydrate, sodium tungstate dihydrate, and trisodium citrate. The content of nickel sulfate hexahydrate in the plating solution was 60 g / L. The content of sodium tungstate dihydrate in the plating solution was 100 g / L. The content of trisodium citrate in the plating solution was 145 g / L. The pH of the plating solution was adjusted to 5.0. The temperature of the plating solution was adjusted to 50°C.

[0044] <Formation of first nickel-containing layer L1> The current density of the first metal layer during electrolytic plating is 2A / dm 2 The electrolytic plating was continued for 1.3 minutes, thereby forming a first nickel-containing layer L1 on the surface of the first metal layer.

[0045] <Formation of second nickel-containing layer L2> Before forming the second nickel-containing layer L2, the first metal layer on which the first nickel-containing layer L1 was formed was immersed in pure water for one minute to clean the surface of the first nickel-containing layer L1. The first metal layer on which the first nickel-containing layer L1 was formed was immersed in the plating solution together with the other electrodes. The current density of the first metal layer during electrolytic plating was set to 3 A / dm 2The electrolytic plating was continued for 0.8 minutes, thereby forming a second nickel-containing layer L2 on the surface of the first nickel-containing layer L1.

[0046] <Formation of third nickel-containing layer L3> Before forming the third nickel-containing layer L3, the first metal layer on which the second nickel-containing layer L2 was formed was immersed in pure water for one minute to clean the surface of the second nickel-containing layer L2. The first metal layer on which the second nickel-containing layer L2 was formed was immersed in the plating solution together with the other electrodes. The current density of the first metal layer during electrolytic plating was 5 A / dm 2 The electrolytic plating was continued for 0.5 minutes, thereby forming a third nickel-containing layer L3 on the surface of the second nickel-containing layer L2.

[0047] The laminate formed by the above plating method was washed by immersing it in pure water for 1 minute. After washing the laminate, the moisture adhering to the laminate was removed. After removing the moisture, the laminate was heat-treated at 110°C for 6 hours.

[0048] By the above method, the laminate of Example 1 was produced. In the case of Example 1, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.

[0049] Example 2 In the case of Example 2, only the first nickel-containing layer L1 was formed on both surfaces of the first metal layer as the second metal layer. In the process of forming the first nickel-containing layer L1 in Example 2, the current density of the first metal layer during electrolytic plating was increased to 2 A / dm 2 From 5A / dm 2 The duration of electrolytic plating in Example 2 was adjusted so that the integrated current of the first metal layer during electrolytic plating was the same as that in Example 1.

[0050] Except for the above, the laminate of Example 2 was produced in the same manner as in Example 1. In the case of Example 2, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.

[0051] Example 3 In the process of forming the first nickel-containing layer L1 in Example 3, the current density of the first metal layer was 2 A / dm 2 and electrolytic plating continued for 1.3 minutes. In the process of forming the second nickel-containing layer L2 in Example 3, the current density of the first metal layer was 3 A / dm 2 and electrolytic plating continued for 0.7 minutes. In the process of forming the third nickel-containing layer L3 in Example 3, the current density of the first metal layer was 4 A / dm 2 and electrolytic plating continued for 0.4 minutes. In the case of Example 3, after the surface of the third nickel-containing layer L3 was washed with pure water, a fourth nickel-containing layer L4 was formed on the surface of the third nickel-containing layer L3. That is, the second metal layer in Example 3 was composed of a first nickel-containing layer L1 laminated directly on the surface of the first metal layer, a second nickel-containing layer L2 laminated directly on the first nickel-containing layer L1, a third nickel-containing layer L3 laminated directly on the second nickel-containing layer L2, and a fourth nickel-containing layer L4 laminated directly on the third nickel-containing layer L3. During the formation of the fourth nickel-containing layer L4, the current density of the first metal layer is 5 A / dm 2 and electrolytic plating continued for 0.2 minutes. Except for the above, the laminate of Example 3 was produced in the same manner as in Example 1. In the case of Example 3, the exposed surface of the fourth nickel-containing layer L4 corresponds to the second surface of the second metal layer.

[0052] Example 4 In the process of forming the first nickel-containing layer L1 in Example 4, the current density of the first metal layer was 2 A / dm 2 and electrolytic plating continued for 5 minutes. In the process of forming the second nickel-containing layer L2 in Example 4, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 0.5 min. In the case of Example 4, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 4 was produced in the same manner as in Example 1. In the case of Example 4, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.

[0053] Example 5 In the case of Example 5, second metal layers were formed on both surfaces of the first metal layer by the following electroless plating, rather than by electrolytic plating. The second metal layers in Example 5 consisted of a first nickel-containing layer L1 laminated directly on the surface of the first metal layer, a second nickel-containing layer L2 laminated directly on the first nickel-containing layer L1, and a third nickel-containing layer L3 laminated directly on the second nickel-containing layer L2.

[0054] <Catalyst treatment> Before the formation of the first nickel-containing layer L1, a catalytic treatment was carried out on the surface of the first metal layer. In the catalytic treatment, the first metal layer was immersed in a catalytic treatment solution for one minute to attach a catalyst (palladium sulfate) to the surface of the first metal layer. The temperature of the catalytic treatment solution was adjusted to 40°C. Axmalta MNK-4-M manufactured by Uemura Kogyo Co., Ltd. was used as the catalytic treatment solution.

[0055] <Formation of first nickel-containing layer L1> In the process of forming the first nickel-containing layer L1, the first metal layer was immersed in an electroless nickel plating solution. The electroless nickel plating solution used in forming the first nickel-containing layer L1 was ICP Nicoron SOF manufactured by Okuno Chemical Industries Co., Ltd. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 85° C. The duration of the electroless plating was 2.5 minutes.

[0056] <Formation of second nickel-containing layer L2> Before forming the second nickel-containing layer L2, the first metal layer on which the first nickel-containing layer L1 was formed was immersed in pure water for 1 minute to clean the surface of the first nickel-containing layer L1. After cleaning the surface of the first nickel-containing layer L1, the surface of the first nickel-containing layer L1 was subjected to catalytic treatment by the above-mentioned method before forming the second nickel-containing layer L2. In the process of forming the second nickel-containing layer L2, the first metal layer on which the first nickel-containing layer L1 was formed was immersed in an electroless nickel plating solution. The electroless nickel plating solution used in forming the second nickel-containing layer L2 was ICP Nicoron GM manufactured by Okuno Chemical Industries Co., Ltd. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 80°C. The duration of the electroless plating was 2.5 minutes.

[0057] <Formation of third nickel-containing layer L3> Before forming the third nickel-containing layer L3, the first metal layer on which the second nickel-containing layer L2 was formed was immersed in pure water for 1 minute to clean the surface of the second nickel-containing layer L2. After cleaning the surface of the second nickel-containing layer L2, the surface of the second nickel-containing layer L2 was subjected to catalytic treatment by the above-mentioned method before forming the third nickel-containing layer L3. In the process of forming the third nickel-containing layer L3, the first metal layer on which the second nickel-containing layer L2 was formed was immersed in an electroless nickel plating solution. The electroless nickel plating solution used in forming the third nickel-containing layer L3 was Top Nicoron LPH manufactured by Okuno Chemical Industries Co., Ltd. The electroless nickel plating solution contained sodium hypophosphite as a reducing agent. The temperature of the electroless nickel plating solution was adjusted to 90°C. The duration of the electroless plating was 2 minutes. After the formation of the third nickel-containing layer L3, the laminate was washed by immersing the laminate in pure water for 1 minute.

[0058] By the above method, the laminate of Example 5 was produced. In the case of Example 5, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.

[0059] Example 6 In the case of Example 6, the third nickel-containing layer L3 was not formed. Except for this, the laminate of Example 6 was produced in the same manner as in Example 5. In the case of Example 6, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.

[0060] Example 7 Electrolytic plating of Example 7 was carried out using a plating solution having a different composition from that of Example 1. The plating solution of Example 7 contained nickel sulfate hexahydrate, nickel chloride hexahydrate, boric acid, trisodium citrate, and sodium hydrogen phosphite. The content of nickel sulfate hexahydrate in the plating solution of Example 7 was 100 g / L. The content of nickel chloride hexahydrate in the plating solution of Example 7 was 30 g / L. The content of boric acid in the plating solution of Example 7 was 30 g / L. The content of trisodium citrate in the plating solution of Example 7 was 30 g / L. The content of sodium hydrogen phosphite in the plating solution of Example 7 was 20 g / L. The pH of the plating solution of Example 7 was adjusted to 3.5. The temperature of the plating solution of Example 7 was adjusted to 60°C.

[0061] In the case of Example 7, only the first nickel-containing layer L1 was formed on both surfaces of the first metal layer as the second metal layer. In the process of forming the first nickel-containing layer L1 in Example 7, the current density of the first metal layer during electrolytic plating was increased to 0.5 A / dm 2 From 4A / dm 2 The duration of electrolytic plating in Example 7 was adjusted so that the integrated current of the first metal layer during electrolytic plating was the same as that in Example 5.

[0062] Except for the above, the laminate of Example 7 was produced in the same manner as in Example 1. In the case of Example 7, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.

[0063] Example 8 The first nickel-containing layer L1 of Example 8 was formed by electrolytic plating using a first plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the first plating solution of Example 8 was 60 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 8 was 30 g / L. The content of trisodium citrate in the first plating solution of Example 8 was 80 g / L. The pH of the first plating solution of Example 8 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 8, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.

[0064] The second nickel-containing layer L2 of Example 8 was formed by electrolytic plating using a second plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the second plating solution of Example 8 was 70 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 8 was 15 g / L. The content of trisodium citrate in the second plating solution of Example 8 was 80 g / L. The pH of the second plating solution of Example 8 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 8, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.

[0065] The third nickel-containing layer L3 of Example 8 was formed by electrolytic plating using a third plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the third plating solution of Example 8 was 70 g / L. The content of sodium tungstate dihydrate in the third plating solution of Example 8 was 8 g / L. The content of trisodium citrate in the third plating solution of Example 8 was 80 g / L. The pH of the third plating solution of Example 8 was adjusted to 7.0. In the process of forming the third nickel-containing layer L3 of Example 8, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.

[0066] Except for the above, the laminate of Example 8 was produced in the same manner as in Example 1. In the case of Example 8, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.

[0067] Example 9 The first nickel-containing layer L1 of Example 9 was formed by electrolytic plating using a first plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the first plating solution of Example 9 was 30 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 9 was 60 g / L. The content of trisodium citrate in the first plating solution of Example 9 was 80 g / L. The pH of the first plating solution of Example 9 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 9, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 3 minutes.

[0068] The second nickel-containing layer L2 of Example 9 was formed by electrolytic plating using a second plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the second plating solution of Example 9 was 40 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 9 was 45 g / L. The content of trisodium citrate in the second plating solution of Example 9 was 80 g / L. The pH of the second plating solution of Example 9 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 9, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 3 minutes.

[0069] In the case of Example 9, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 9 was produced in the same manner as in Example 1. In the case of Example 9, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.

[0070] Example 10 The first nickel-containing layer L1 of Example 10 was formed by electrolytic plating using a first plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the first plating solution of Example 10 was 70 g / L. The content of sodium tungstate dihydrate in the first plating solution of Example 10 was 15 g / L. The content of trisodium citrate in the first plating solution of Example 10 was 80 g / L. The pH of the first plating solution of Example 10 was adjusted to 7.0. In the process of forming the first nickel-containing layer L1 of Example 10, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 2 minutes.

[0071] The second nickel-containing layer L2 of Example 10 was formed by electrolytic plating using a second plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the second plating solution of Example 10 was 70 g / L. The content of sodium tungstate dihydrate in the second plating solution of Example 10 was 8 g / L. The content of trisodium citrate in the second plating solution of Example 10 was 80 g / L. The pH of the second plating solution of Example 10 was adjusted to 7.0. In the process of forming the second nickel-containing layer L2 of Example 10, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.

[0072] The third nickel-containing layer L3 of Example 10 was formed by electrolytic plating using a third plating solution having a different composition from the plating solution of Example 1. The content of nickel sulfate hexahydrate in the third plating solution of Example 10 was 70 g / L. The content of sodium tungstate dihydrate in the third plating solution of Example 10 was 4 g / L. The content of trisodium citrate in the third plating solution of Example 10 was 80 g / L. The pH of the third plating solution of Example 10 was adjusted to 7.0. In the process of forming the third nickel-containing layer L3 of Example 10, the current density of the first metal layer was 5 A / dm 2 and electrolytic plating continued for 1 minute.

[0073] Except for the above, the laminate of Example 10 was produced in the same manner as in Example 1. In the case of Example 10, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.

[0074] Example 11 In the case of Example 11, the first nickel-containing layer L1 and the second nickel-containing layer L2 were formed by only one electrolytic plating as follows. The content of nickel sulfate hexahydrate in the plating solution of Example 11 was 80 g / L. The content of sodium tungstate dihydrate in the plating solution of Example 11 was 5 g / L. The content of trisodium citrate in the plating solution of Example 11 was 80 g / L. The pH of the plating solution of Example 11 was adjusted to 7.0. The current density of the first metal layer during electrolytic plating of Example 11 was 5 A / dm 2 The electrolytic plating of Example 11 continued for 3 minutes. During the electrolytic plating of Example 11, the plating bath was stationary without being agitated. Although the reason why two layers having different nickel contents were formed in Example 11 is not clear, it is believed that the first nickel-containing layer L1 and the second nickel-containing layer L2 were formed by the following mechanism. The content of sodium tungstate dihydrate in the plating solution of Example 11 was adjusted to be lower than that of the plating solution of Example 1. The concentration of the tungsten component is locally reduced near the plated object due to plating precipitation. However, since the content of sodium tungstate dihydrate in the plating solution of Example 11 was lower than that of the plating solution of Example 1, the concentration gradient of the tungsten component near the plated object was significantly suppressed. Therefore, the supply of the tungsten component to the second metal layer was suppressed. Furthermore, since the plated object was kept stationary without being rocked, the stirring effect due to rocking in the plating solution was suppressed, and the supply of the tungsten component to the second metal layer was further suppressed. As a result, a first nickel-containing layer L1 having a relatively large tungsten content was formed at the beginning of plating, and then a second nickel-containing layer L2 having a relatively small tungsten content was formed. In the case of Example 11, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 11 was produced in the same manner as in Example 1. In the case of Example 11, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.

[0075] Example 12 In the case of Example 12, the first nickel-containing layer L1 and the second nickel-containing layer L2 were formed by only one electrolytic plating as follows. The content of nickel sulfate hexahydrate in the plating solution of Example 12 was 80 g / L. The content of sodium tungstate dihydrate in the plating solution of Example 12 was 3 g / L. The content of trisodium citrate in the plating solution of Example 12 was 80 g / L. The pH of the plating solution of Example 12 was adjusted to 7.0. The current density of the first metal layer during electrolytic plating of Example 12 was 5 A / dm 2 The electrolytic plating of Example 12 continued for 3 minutes. During the electrolytic plating of Example 12, the plating bath was stationary without being agitated. The content of sodium tungstate dihydrate in the plating solution in Example 12 was adjusted to be lower than the content of sodium tungstate dihydrate in the plating solution in Example 11. As a result, a first nickel-containing layer L1 containing tungsten was formed at the initial stage of plating, and then a second nickel-containing layer L2 not containing tungsten was formed. In the case of Example 12, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 12 was produced in the same manner as in Example 1. In the case of Example 12, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.

[0076] Example 13 In the case of Example 13, the first nickel-containing layer L1 and the second nickel-containing layer L2 were formed by only one electrolytic plating as follows. The content of nickel sulfate hexahydrate in the plating solution of Example 13 was 80 g / L. The content of sodium tungstate dihydrate in the plating solution of Example 13 was 1 g / L. The content of trisodium citrate in the plating solution of Example 13 was 80 g / L. The pH of the plating solution of Example 13 was adjusted to 7.0. The current density of the first metal layer during electrolytic plating of Example 13 was 5 A / dm 2 The electrolytic plating of Example 13 continued for 3 minutes. During the electrolytic plating of Example 13, the plating bath was stationary without being agitated. As in Example 12, the content of sodium tungstate dihydrate in the plating solution in Example 13 was adjusted to be lower than the content of sodium tungstate dihydrate in the plating solution in Example 11. As a result, a first nickel-containing layer L1 containing tungsten was formed at the initial stage of plating, and then a second nickel-containing layer L2 not containing tungsten was formed. In the case of Example 13, the third nickel-containing layer L3 was not formed. Except for the above, the laminate of Example 13 was produced in the same manner as in Example 1. In the case of Example 13, the exposed surface of the second nickel-containing layer L2 corresponds to the second surface of the second metal layer.

[0077] Comparative Example 1 In the case of Comparative Example 1, only the first nickel-containing layer L1 was formed as the second metal layer on both surfaces of the first metal layer. Electrolytic plating of Comparative Example 1 was performed using a plating solution having a different composition from that of Example 1. The plating solution of Comparative Example 1 contained nickel sulfate hexahydrate, nickel chloride hexahydrate, and boric acid. The content of nickel sulfate hexahydrate in the plating solution of Comparative Example 1 was 240 g / L. The content of nickel chloride hexahydrate in the plating solution of Comparative Example 1 was 45 g / L. The content of boric acid in the plating solution of Comparative Example 1 was 30 g / L. The pH of the plating solution was adjusted to 4.2. The temperature of the plating solution was adjusted to 40°C. In the process of forming the first nickel-containing layer L1 in Comparative Example 1, the current density of the first metal layer during electrolytic plating was 5 A / dm 2and electrolytic plating continued for 1.5 minutes.

[0078] Except for the above, the laminate of Comparative Example 1 was produced in the same manner as in Example 1. In the case of Comparative Example 1, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.

[0079] Comparative Example 2 In the case of Comparative Example 2, only the first nickel-containing layer L1 was formed as the second metal layer on both surfaces of the first metal layer. In the case of Comparative Example 2, the current density of the first metal layer during electrolytic plating was 5 A / dm 2 The electrolytic plating was continued for 2 minutes, thereby forming a first nickel-containing layer L1 on the surface of the first metal layer.

[0080] Except for the above, the laminate of Comparative Example 2 was produced in the same manner as in Example 1. In the case of Comparative Example 2, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.

[0081] Comparative Example 3 In the case of Comparative Example 3, only the first nickel-containing layer L1 was formed as the second metal layer on both surfaces of the first metal layer. In the process of forming the first nickel-containing layer L1 in Comparative Example 3, the duration of electroless plating was 7 minutes.

[0082] Except for the above, the laminate of Comparative Example 3 was produced in the same manner as in Example 5. In the case of Comparative Example 3, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.

[0083] Comparative Example 4 In the process of forming the first nickel-containing layer L1 in Comparative Example 4, the duration of electroless plating was 15 minutes.

[0084] Except for the above, the laminate of Comparative Example 4 was produced in the same manner as in Comparative Example 3. In the case of Comparative Example 4, the exposed surface of the first nickel-containing layer L1 corresponds to the second surface of the second metal layer.

[0085] Comparative Example 5 In the process of forming the first nickel-containing layer L1 in Comparative Example 5, the current density of the first metal layer during electrolytic plating was 5 A / dm 2 and electrolytic plating continued for 0.2 minutes. In the process of forming the second nickel-containing layer L2 in Comparative Example 5, the current density of the first metal layer during electrolytic plating was 4 A / dm 2 and electrolytic plating continued for 0.4 minutes. In the process of forming the third nickel-containing layer L3 in Comparative Example 5, the current density of the first metal layer during electrolytic plating was 3 A / dm 2 The electrolytic plating was continued for 0.7 minutes.

[0086] Except for the above, a laminate of Comparative Example 5 was produced in the same manner as in Example 1. In the case of Comparative Example 5, the exposed surface of the third nickel-containing layer L3 corresponds to the second surface of the second metal layer.

[0087] [Laminate analysis] The laminates of Examples 1 to 13 and Comparative Examples 1 to 5 were analyzed by the following method.

[0088] The laminate was cut in the lamination direction (the direction perpendicular to the first surface of the second metal layer). The cross section of the laminate was observed with a scanning electron microscope (SEM). The composition of the second metal layer exposed in the cross section of the laminate was analyzed by energy dispersive X-ray spectroscopy (EDS) along the thickness direction D of the second metal layer.

[0089] It was confirmed that the second metal layers of each of Examples 1 to 13 and Comparative Examples 1 to 5 contained the constituent elements shown in Table 1 below.

[0090] The Ni content [Ni] in each nickel-containing layer constituting the second metal layer in each of Examples 1 to 13 and Comparative Examples 1 to 5 is shown in Table 1 below. L1 in Table 1 means the first nickel-containing layer. L2 in Table 1 means the second nickel-containing layer. L3 in Table 1 means the third nickel-containing layer. L4 in Table 1 means the fourth nickel-containing layer. Except for Examples 2 and 7, the Ni content [Ni] in each nickel-containing layer was approximately constant.

[0091] In the cases of Examples 2 and 7, the Ni content [Ni] in the second metal layer (first nickel-containing layer L1) continuously increased along the thickness direction D of the second metal layer. That is, in the cases of Examples 2 and 7, the Ni content in the second metal layer was minimum near the first surface of the second metal layer and maximum near the second surface of the second metal layer. In the case of Example 2, the minimum Ni content in the second metal layer was 62 mass %, and the maximum Ni content in the second metal layer was 69 mass %. In the case of Example 7, the minimum Ni content in the second metal layer was 87 mass %, and the maximum Ni content in the second metal layer was 99 mass %.

[0092] The Δ[Ni] of each of Examples 1 to 13 and Comparative Example 5 is shown in the following Table 1. The definition of Δ[Ni] is as described above.

[0093] In all of Examples 1 to 13 and Comparative Examples 1 to 5, the thickness of each nickel-containing layer constituting the second metal layer was uniform. The thickness of each nickel-containing layer was measured in the cross section of the laminate. The thickness of each nickel-containing layer is shown in Table 1 below.

[0094] [Bending test] The following bending test according to JISC5016 was carried out using each of the laminates of Examples 1 to 13 and Comparative Examples 1 to 5. The outline of the bending test is shown in FIG.

[0095] The laminate 10 used in the bending test had a rectangular shape. The length of the long side of the laminate 10 (the length of the laminate 10 in the direction perpendicular to the lamination direction) was 150 mm. The length of the short side of the laminate 10 (the width of the laminate in the direction perpendicular to the lamination direction) was 50 mm.

[0096] A cylinder 14 harder than the laminate 10 was used in the bending test. The height of the cylinder 14 was greater than the length of the short side of the laminate 10. The radius of curvature R of the outer circumferential surface of the cylinder 14 was 5 mm.

[0097] The outer peripheral surface of the cylinder 14 was in contact with the center of the laminate 10 in the long side direction of the laminate 10 so that the height direction of the cylinder 14 was parallel to the short side of the laminate 10. The laminate 10 was folded so that the surface of the laminate 10 (the second surface of the second metal layer) was in close contact with the outer peripheral surface of the cylinder 14. One end 12 of the folded laminate 10 was fixed in a jig 13. The other end 15 of the folded laminate 10 was repeatedly moved back and forth along direction B (the long side direction of the laminate 10) for one minute. The moving distance of the end 15 was 30 mm. The cycle of the reciprocation was 150 times / min.

[0098] After the end 15 of the laminate 10 was repeatedly moved back and forth for one minute, the surface resistivity SR (unit: Ω / sq) was measured at the portion of the laminate 10 that was in close contact with the outer circumferential surface of the cylindrical body 14 (the second surface of the second metal layer). The surface resistivity SR was measured by a four-terminal method. The surface resistivity SR0 was also measured before the above-mentioned bending test. The portion where SR0 was measured before the bending test was the same as the portion where SR was measured. The surface resistance increase rate ΔSR (unit: %) defined by the following mathematical formula 1 was calculated. ΔSR = 100 × (SR - SR0) / SR0 (1)

[0099] In the bending test, tensile stress acts on the surface of the laminate 10 (the second surface of the second metal layer) that is in close contact with the outer circumferential surface of the cylinder 14. The more cracks formed in the laminate 10 (second metal layer) due to this tensile stress and the larger the cross-sectional area formed by the cracks, the higher the surface resistance increase rate ΔSR. In other words, the higher the tensile strength of the laminate 10, the more easily cracks in the laminate 10 (second metal layer) are suppressed, and the lower the surface resistance increase rate ΔSR.

[0100] The results of the bending test for each of the above-mentioned Examples 1 to 13 and Comparative Examples 1 to 5 are shown in Table 1 below. A in Table 1 means that the surface resistance increase rate ΔSR is 0% or more and less than 5%. B in Table 1 means that the surface resistance increase rate ΔSR is 5% or more and less than 10%. C in Table 1 means that the surface resistance increase rate ΔSR is 10% or more and less than 15%. D in Table 1 means that the surface resistance increase rate ΔSR is 15% or more.

[0101] [Table 1] [Industrial Applicability]

[0102] For example, the laminate according to one aspect of the present invention may be used as a negative electrode current collector of a lithium ion secondary battery. [Explanation of symbols]

[0103] 1...first metal layer, 2...second metal layer, 3...negative electrode active material layer, 10...laminated body (current collector), 20...negative electrode, D...thickness direction of second metal layer, S1...first surface of second metal layer, S2...second surface of second metal layer.

Claims

1. a first metal layer comprising copper; a second metal layer comprising nickel and laminated directly to the first metal layer; Equipped with the first surface of the second metal layer is in contact with the first metal layer; a second surface of the second metal layer that is opposite to the first surface; a thickness direction of the second metal layer is substantially perpendicular to the first surface and extends from the first surface to the second surface; The unit of the nickel content in the second metal layer is mass %, the nickel content of the second metal layer increases along the thickness direction; The thickness of the first metal layer is represented as T1; The thickness of the second metal layer is designated T2; T2 / T1 is 0.6 or more and 1.0 or less; Laminate.

2. The second metal layer further contains at least one element selected from the group consisting of phosphorus and tungsten. The laminate according to claim 1 .

3. the second metal layer is made of a plurality of nickel-containing layers stacked in the thickness direction, The nickel content of each of the plurality of nickel-containing layers is different from each other; The laminate according to claim 1 or 2.

4. the nickel content of the second metal layer is lowest near the first surface, increases stepwise along the thickness direction, and is highest near the second surface; The laminate according to any one of claims 1 to 3.

5. the nickel content of the second metal layer is lowest near the first surface, increases continuously along the thickness direction, and is highest near the second surface; The laminate according to any one of claims 1 to 3.

6. A laminate according to any one of claims 1 to 5, Negative electrode current collector for lithium-ion secondary batteries.

7. The negative electrode current collector according to claim 6 , a negative electrode active material layer including a negative electrode active material; Equipped with the negative electrode active material layer is laminated directly on the second surface of the second metal layer; A negative electrode for lithium-ion secondary batteries.

8. The negative electrode active material contains silicon. The negative electrode according to claim 7.

Citation Information

Patent Citations

  • High-phosphorus nickel plating method

    JP1990194182A

  • Negative electrode current collector for nonaqueous electrolytic solution secondary battery

    JP2005197205A

  • JP2005‐197205A

  • COPPER FOIL FOR Li BATTERY COLLECTOR, ELECTRODE FOR Li BATTERY USING THE SAME, AND Li BATTERY

    JP2013077462A

  • Electrostatic sensor

    JP2015114690A